Advancing Sustainable Development Goal 6: Innovations, Challenges, and Pathways for Clean Water and Sanitation - Jackson, Msafiri Mmamba; Alfaki, Amjd Abdallah Omer (Integrated Science Education Journal, 2025)
Purpose of the study: The aim of this research is to analyze the global state of clean water and sanitation, identify the main challenges faced, and explore innovative solutions and strategies that can contribute to the achievement of Sustainable Development Goal 6 by 2030. Methodology: This study employed a systematic literature review and comparative analysis with secondary data from WHO, UNICEF, and the World Bank. Data collection was conducted through international databases such as Scopus, Web of Science, and Google Scholar. Data analysis was conducted using descriptive quantitative analysis and thematic qualitative analysis using a matrix-based instrument. Main Findings: Research shows that more than 2.2 billion people still lack access to safe drinking water and 3.4 billion people lack adequate sanitation services, with the greatest disparities occurring in Sub-Saharan Africa and South Asia. Innovations such as smart water monitoring, low-cost filtration, rainwater harvesting, and community-based sanitation programs have proven to have significant impact. However, persistent barriers include limited funding, social inequality, climate change, and weak governance. Novelty/Originality of this study: This research integrates technological innovation, public health approaches, community participation, and policy frameworks into a comprehensive analysis of clean water and sanitation. Unlike previous research that focused solely on technical or health aspects, this study expands knowledge by mapping multidimensional strategies and providing practical recommendations for policymakers and stakeholders.